Repayment policy for multiple loans, Yasmín A. Ríos-Solís, Mario A. Saucedo-Espinosa, Gabriel A. Caballero-Robledo, detailed data - Ríos Solís, Yasmín Agueda; Saucedo Espinosa, Mario Alberto; Caballero Robledo, Gabriel A.
The zip contains the instances. Archive How to red the instances explains how to read the instances of the zip file The excel corresponds to the solutions of our model and the other models of the literature.